Fabrication of zinc oxide low voltage varistor ceramics added Bi, Ti, Sb, and Al by conventional and solution coating method - Mohammadi, Raheleh (2017)
The Zinc Oxide (ZnO) based varistor ceramics, an electrical protective device from transient voltage surge, have become technologically important because of their highly nonlinear electrical characteristics enabling them to be used as reversible, solid-state switches with large-energy-handling capabilities. The aim of the present study is to optimize the soaking time, in order to maximize an electrical non-linear coefficient (α) of the varistor ceramics fabricated by the conventional ball milling, and the solution coating methods. In addition, the electrical property and microstructure of Bi2O3, Al2O3, TiO2 and Sb2O3 additives in (ZnO) based varistor ceramics at the various soaking time. In preparing the ceramic by the solution coating method, bismuth oxide, titanium oxide, and aluminium oxide were prepared by from bismuth nitrate, titanium botoxide, and aluminium nitrate, respectively. The electrical property, microstructure and thermal characterisation of the ceramic were carried out by J-E measurement, XRD, EDX, FESEM, FTIR, and TGA analyses. The results from initial powders show that homogenously mixed ZnO powder could be made readily by coating ZnO powder with a solution of additives. The varistor ceramics prepared from the solution coating method reveal a higher α value and lower break down voltage than those provided by the ball milling routes. The improved J-E properties of varistor ceramic made by this methods could be attributed to the homogenous distribution of additives in the starting powder. The effect can produce a similar profile of additives distributions at each grain-grain boundary regions across the whole microstructure. Similar composition at each grain boundary region, which could be created uniform trapping centres that lastly resulted in the formation of the uniform potential barrier through the microstructure and consequently better electrical properties. As a comparative result of the technique of fabrication, the solution coating method has better homogenous. The maximum electrical property of the varistor ceramic was at soaking time of 150 min (sintered at 1250°C) with the α value around 16.38 and 10.73 for the solution coating and for the ball milling methods, respectively.